Pro-Inflammatory Adaptive Cytokines and Shed Tumor Necrosis Factor Receptors are Elevated Preceding Systemic Lupus Erythematosus Disease Flare - Munroe, Melissa E. (2014)
OBJECTIVE: Systemic lupus erythematosus (SLE) is a multifaceted disease characterized by immune dysregulation and unpredictable disease activity. This study evaluated changes in plasma concentrations of soluble mediators preceding clinically-defined disease flares. METHODS: Soluble mediators (n=52) were examined, including cytokines, chemokines, and soluble receptors, using validated multiplex bead-based or enzyme-linked immunosorbent assays in plasma from European American SLE patients who developed disease flare 6 or 12 weeks after baseline assessment were compared to 28 matched SLE patients without impending flare and 28 matched healthy controls (n=84). For a subset, mediators within samples preceding SLE disease flare and during a clinically stable period from the same individual were compared. RESULTS: Compared to clinically stable patients, patients with impending flare had significant (p≤0.01) alterations in 27 soluble mediators at baseline with significantly higher levels of pro-inflammatory mediators, including Th1, Th2, and Th17-type cytokines, several weeks before clinical flare. Baseline levels of regulatory cytokines, including IL-10 and TGF-β, were higher in non-flare SLE patients, while baseline levels of soluble TNFRI, TNFRII, Fas, FasL, and CD40L were significantly greater in pre-flare patients (p≤0.002). A normalized and weighted combined soluble mediator score was significantly higher in pre-flare SLE patients versus those with stable disease (p≤0.0002). CONCLUSION: Pro-inflammatory adaptive cytokines and shed TNF receptors, are elevated prior to disease flare, while regulatory mediators are elevated during periods of stable disease. Alterations in the balance between inflammatory and regulatory mediators may help identify patients at risk of disease flare and help decipher SLE pathogenic mechanisms.